DEVELOPMENT OF INNOVATIVE ENTREPRENEURSHIP IN KAZAKHSTAN: TRENDS AND PROSPECTS - G.T. Kunurkulzhaeva,; G.K. Demeuova,; B.Z. Zhumagalieva, (Academic Journal of Physical and Chemical Sciences, 2019)
According to the authors, the success of many innovative projects, the growth of innovative products depends on measures to extend the life cycle of the innovative product - “newly introduced or undergoing significant technological changes”. Analysis of economic development in Kazakhstan shows that innovation in the country plays a large role. At the same time, it should be noted that innovation activity in the republic is not yet a source of increasing the country's competitiveness in the world market. Despite the positive experience of a number of initiatives, a significant breakthrough in the field of innovative development of the country's economy did not occur.